1987
DOI: 10.1111/j.1472-8206.1987.tb00576.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF VARIOUS PHARMACOLOGICAL AGENTS ON ISOLATED HUMAN BRONCHIAL AND PULMONARY ARTERIAL AND VENOUS MUSCLE PREPARATIONS CONTRACTED BY LEUKOTRIENE D4

Abstract: The response of isolated human bronchial muscle preparations to leukotriene D4 (LTD4, 0.1 microM; 0.22 +/- 0.03 g/mm2) was similar to that of histamine (50 microM; 0.21 +/- 0.02 g/mm2). Isolated pulmonary venous preparations also contracted to these same concentrations of both agonists (LTD4, 0.32 +/- 0.19 g/mm2; and histamine, 0.36 +/- 0.07 g/mm2). However, pulmonary arterial preparations responded to histamine (50 microM, 0.59 +/- 0.10 g/mm2) but exhibited a reduced response to LTD4 (0.3 microM, 0.06 +/- 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Previous reports (Hanna et al ., 1981; Schellenberg & Foster, 1984; Bourdillat et al ., 1987) have demonstrated that human isolated pulmonary arteries exhibited only a small response when stimulated by cysLTs. These observations were recently confirmed by Bäck et al .…”
Section: Discussionmentioning
confidence: 89%
“…Previous reports (Hanna et al ., 1981; Schellenberg & Foster, 1984; Bourdillat et al ., 1987) have demonstrated that human isolated pulmonary arteries exhibited only a small response when stimulated by cysLTs. These observations were recently confirmed by Bäck et al .…”
Section: Discussionmentioning
confidence: 89%
“…times more potent. The data reported indicate that the agonist potencies for relaxation of human vascular preparations (pEC 50 values, approximately, 11-10) (Allen et al, 1992;Ortiz et al, 1995) are markedly different from the potencies required to produce contractions in the same tissue (pEC 50 values, approximately, 9 -7) (Schellenberg and Foster, 1984;Bourdillat et al, 1987;Allen et al, 1992;Labat et al, 1992;Ortiz et al, 1995;StankeLabesque et al, 2000). Such data suggest that either the receptors on the endothelium associated with the relaxation are different from the receptors responsible for the contraction or the G-protein second messengers may be coupled more efficiently.…”
Section: Vascular Smooth Muscle Contractionmentioning
confidence: 99%
“…Collectively, the results with these chemically distinct antagonists (Table 5) provided pertinent pharmacological support for the presence of two receptors in the various tissue preparations. Hanna et al (1981) reported that cys-LTs contracted not only isolated human airways but also human pulmonary veins and noted that the maximum responses on human pulmonary arteries were small (Schellenberg and Foster, 1984;Bourdillat et al, 1987). Berkowitz et al (1984) studied vascular preparations from several species (rat, rabbit, and guinea pig) and observed small contractions in guinea pig pulmonary veins, the inferior vena cava and jugular vein; the effects of LTC 4 were not examined.…”
Section: B Cysteinyl-leukotriene Functional Studiesmentioning
confidence: 99%
“…A considerable amount of evidence has been published demonstrating the contractile effects of leukotrienes (LT) in a variety of smooth muscle preparations from several animal species including man (Dahlen et al, 1980;Hanna et al, 1981;Buckner et al, 1986;Bourdillat et al, 1987). However, LT are also known to produce endothelium-dependent relaxations in vessels from different species (Burke et al, 1982;Secrest et al, 1985;Sakuma & Levi, 1988).…”
Section: Introductionmentioning
confidence: 99%